Thrill of the Chaste The Pursuit of 'Love' as the Perpetual Dialectic between the 'Real' and the 'Ideal Image' in Kierkegaard's The Seducer's Diary - Edwards, Aaron (2016)
This article will explicate an intriguing dynamic found in Kierkegaard's The Seducer's Diary , in which the protagonist's ideal image of love is wilfully perpetuated over its experienced reality. This is a rich literary depiction in its own right, whilst also bearing a number of interesting corollaries. There are oft-noted connotations between the 'Seducer's Diary' and Kierkegaard's own broken engagement, which will be shown; but there are also significant parallels with Goethe's The Sorrows of Young Werther , which depicts a remarkably similar dialectic of perpetuated 'imagistic' idealism. Kierkegaard's later expression of an explicitly theological account of love counteracts this earlier portrayal of love-as-ideality. Yet Kierkegaard cannot entirely escape the 'love' of The Seducer's Diary in which the self-imposed mythical image conquers the lover's own reality. This remains a fascinating tension within Kierkegaard's conception of love, which renders some cautiously interesting theological applications to this text. One of these may be found, in particular, in the way in which the Seducer's dialectical rejection of 'actuality' might mirror that of Christendom's rejection of real 'encounter' with God.